2020
DOI: 10.1186/s12912-020-00434-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between clinical dishonesty and perceived clinical stress among nursing students in southeast of Iran

Abstract: Background: Clinical dishonesty is a complex problem that threatens the health and safety of patients. This study aimed to investigate the relationship between clinical dishonesty and perceived clinical stress in nursing students. Method: This cross-sectional correlational study was conducted on 395 nursing students from 4 nursing colleges. The data were collected using a demographic information questionnaire, Nursing Student ' s Perception of Clinical Stressors, and a 12-item researcher-made questionnaire to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…These results are worrisome and may reflect the great burden of self-charge and stress associated with women during undergraduate studies to ensure a better performance in their professional careers (Sadir et al, 2010). In line with this, a recent study of 395 Iranian nursing students found a higher prevalence of professional misconduct among women and a positive correlation with perceived stress (Rafati et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These results are worrisome and may reflect the great burden of self-charge and stress associated with women during undergraduate studies to ensure a better performance in their professional careers (Sadir et al, 2010). In line with this, a recent study of 395 Iranian nursing students found a higher prevalence of professional misconduct among women and a positive correlation with perceived stress (Rafati et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, academic misconduct such as plagiarism, cheating on tests, individual use of collective academic material, and unauthorized recording of classes are commonly observed (Anderson & Obenshain, 1994;Gitanjali, 2004;Sousa et al, 2016). These attitudes, during the training phase, can be associated with inappropriate behavior in clinical-professional settings (Rafati et al, 2020;Satterwhite, 2000). Thus, the teaching of ethics in medical training is still a topic of global concern, since it is potentially harmful to the professional behavior of future physicians (Mubeen et al, 2017;Sousa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other U.S. nursing research studies heralded similar results in that there were high incidences of cheating reported amongst nursing students, and these incidences were occurring both in the classroom and WIL settings (Krueger 2014;McClung & Gaberson 2020;McClung & Kraenzle Schneider, 2018;McCrink, 2010). Similar findings have been reported through the international nursing literature and amplify the need to understand how such behaviour and conduct impacts the effectiveness of nursing education locally and globally (Ali et al, 2018;Keçeci et al, 2011;Lovric et al, 2020;Macale, 2017;Rafati et al, 2020).…”
Section: Nursing and Departures From Academic Integrity Literaturesupporting
confidence: 55%
“…The rapid development of modern technology and the pervasive phenomenon of credentialism and academic inflation 1,2 seem to contribute to a significant increase in unethical and academic dishonest behaviour among nursing students worldwide. [3][4][5][6][7] Credentialism and educational inflation encompass a number of interrelated processes that include excessive formal demands and 'inflated' needs for high grades for the purpose of academic and professional success, increased chance of employment and career advancement. The mentioned competition policy performs additional pressure on students who strive to achieve excellent grades at all costs.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned competition policy performs additional pressure on students who strive to achieve excellent grades at all costs. [3][4][5][6][7] Academic dishonesty in higher education is a widespread, insidious and global problem. 8 In higher education, nursing programmes can have profound negative implications for the clinical setting.…”
Section: Introductionmentioning
confidence: 99%